Community-led research : walking new pathways together. - Rawlings, Victoria; Flexner, James; Riley, Lynette (Sydney University Press : University of Sydney, 2021)
The concept of community-led research has taken off in recent years in a variety of fields, from archaeology and anthropology to social work and everything in between. Drawing on case studies from Australia, the Pacific and Southeast Asia, this book considers what it means to participate in community-led research, for both communities and researchers. How can researchers and communities work together well, and how can research be reimagined using the knowledge of First Nations peoples and other communities to ensure it remains relevant, sustainable, socially just and inclusive?